Implications of the Russian Invasion on Ukrainians' Pornography Consumption: Insights from Big-Data Processing. - Nessaibia, Issam; Howard, Alper; Bouarroudj, Tayeb (Archives of Sexual Behavior, 2025)
The invasion of Ukraine by Russia in 2022 has led to drastic changes in the social distancing awareness of Ukrainians and affected their social relationships. Due to the large-scale international conflict, fear of death and social distancing arose from the perception of external dangers caused by Russian army attacks, leading to the anticipation that sexual activities would be severely impacted. However, retrospective self-report studies on Ukrainians' pornography consumption and autoeroticism during this war are sorely lacking. This study used big-data databases available on the Internet to investigate factors that affected pornography use during the Russia–Ukraine War. Weekly relative search volume (WRSV) data from Google Trends from January 2, 2022 to July 31, 2022, were extracted. Pornography habits data were extracted from the Pornhub Insights website. The parameter was defined as "Ukraine's most searched-for terms in 2022 compared to an average day in 2021." A cumulative number of civilian deaths in Ukraine during Russia's invasion (listed by week) was obtained from the Office of the High Commissioner for Human Rights (OHCHR) website (ohchr.org). The normality of the data was examined using the Shapiro–Wilk test. All variables included in this study were normally distributed. Therefore, parametric tests were adopted where appropriate. According to Google Trends, the WRSV for "pornography" increased in early March 2022 for the Ukrainian people, which is close to the date when Russia invaded and occupied parts of Ukraine in a major escalation of the Russo-Ukrainian War on February 24, 2022. The number of weekly civilian war deaths was positively correlated with the traffic of Pornhub, a popular pornography website in Ukraine, and the WRSV for "pornography." Mediation analysis demonstrated that a stronger Russian–pornography use association was observed with increased social distancing awareness. Increased Ukrainian pornography consumption during the 2022 invasion was observed, and it was associated with the severity of the Russian army attacks. Social distancing awareness could be a key factor influencing interest in and use of pornography for the Ukrainians. Further studies on changes in sexual desire and birth rate control in Ukraine are warranted, as long-term public health may be affected by shifts in sexual behavior during the Russo-Ukrainian War.